“If it weren’t for COVID-19…”: Counterfactual arguments influence support for climate change policies via cross-domain moral licensing or moral consistency effects - Bertolotti, Mauro; Valla, Luca Guido; Catellani, Patrizia (Frontiers in Psychology, 2022)
In two studies, we investigated whether counterfactual messages (i.e., “If… then…”) on the economic costs of past public policies influence support for future climate change policies. In Study 1, we tested whether the effect of upward counterfactual messages depended on their referring (or not) to the COVID-19 pandemic. Results showed lower support for a future climate change policy when the past expenses evoked by the upward counterfactual messages were attributed to COVID-19. In Study 2, we combined upward counterfactuals with downward counterfactuals presenting past economic efforts to deal with the COVID-19 pandemic as a moral credit. Results showed that exposure to downward counterfactuals decreased support for climate change policies among participants with low endorsement of anti-COVID-19 measures, whereas it increased support among participants with high endorsement. Discussion focuses on the conditions under which counterfactual communication may activate cross-dimensional moral licensing or moral consistency effects, influencing support for climate change policies.